Spectral Music and the Appeal to Nature. Issue 1 (26th April 2018) - O'CALLAGHAN, JAMES
Abstract: Discourse surrounding spectral music frequently makes reference to nature and related language. Practitioners, theorists, and musicologists have discussed different aspects and perspectives on the idea of nature in the relation to this music and it is not always clear that these terms are used in the same way. This article examines the different meanings of 'nature' applied to various concepts and techniques in spectral music, the extent to which these descriptors may be misleading, and the cultural context and possible motivations for the use of this kind of rhetoric. Through a discussion of the derivation structure in spectral music, a focus on human perception, metaphorical references to nature, the rhetoric surrounding the harmonic series and instrumental (re)synthesis, and finally mimetic references to nature in music using spectral techniques (including a discussion of the music of François-Bernard Mâche), the article endeavours to provide a thorough survey of the subject.